Aminophylline at clinically relevant concentrations affects inward rectifier potassium current in healthy porcine and failing human cardiomyocytes in a similar manner - Bébarová, Markéta; Švecová, Olga; Kula, Roman; Pásek, Michal; Jeklová, Edita; Fila, Petr; Pešl, Martin (Biomedicine & pharmacotherapy, 2024)
Aminophylline, a bronchodilator mainly used to treat severe asthma attacks, may induce arrhythmias. Unfortunately, the underlying mechanism is not well understood. We have recently described a significant, on average inhibitory effect of aminophylline on inward rectifier potassium current IK1, known to substantially contribute to arrhythmogenesis, in rat ventricular myocytes at room temperature. This study was aimed to examine whether a similar effect may be observed under clinically relevant conditions. Experiments were performed using the whole cell patch clamp technique at 37°C on enzymatically isolated healthy porcine and failing human ventricular myocytes. The effect of clinically relevant concentrations of aminophylline (10-100 µM) on IK1 did not significantly differ in healthy porcine and failing human ventricular myocytes. IK1 was reversibly inhibited by ∼20 and 30 % in the presence of 30 and 100 µM aminophylline, respectively, at -110 mV; an analogical effect was observed at -50 mV. To separate the impact of IK1 changes on AP configuration, potentially interfering ionic currents were blocked (L-type calcium and delayed rectifier potassium currents). A significant prolongation of AP duration was observed in the presence of 100 µM aminophylline in porcine cardiomyocytes which well agreed with the effect of a specific IK1 inhibitor Ba2+ (10 µM) and with the result of simulations using a porcine ventricular cell model. We conclude that the observed effect of aminophylline on healthy porcine and failing human IK1 might be involved in its proarrhythmic action. To fully understand the underlying mechanism, potential aminophylline impact on other ionic currents should be explored.
Keywords: Animals; vztah mezi dávkou a účinkem léčiva; Heart Ventricles; aminofylin; Myocytes, Cardiac; Action Potentials; srdeční komory; Heart Failure; lidé; srdeční selhání; prasata; Dose-Response Relationship, Drug; Male; Human; Swine; draslíkové kanály dovnitř usměrňující; Potassium Channels, Inwardly Rectifying; Pig; Patch-Clamp Techniques; Aminophylline; zvířata; metoda terčíkového zámku; mužské pohlaví; Inward rectifier; Action potential; Arrhythmia; akční potenciály; kardiomyocyty; Humans